2022
DOI: 10.1039/d2qm00338d
|View full text |Cite
|
Sign up to set email alerts
|

Low-bandgap small molecule acceptors with asymmetric side chains

Abstract: Two low-bandgap ADA small molecule acceptors A1 and A2 with asymmetric out-of-plane side chains were synthesized. Different from previous works, the asymmetric side chains of A1 and A2 were installed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…[ 32‐33 ] Since 2015, many advanced NFAs with good photovoltaic properties have been reported, in large part due to the tremendous efforts that have been put into the design and synthesis of novel π‐conjugated fused‐ring cores. [ 34‐38 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 32‐33 ] Since 2015, many advanced NFAs with good photovoltaic properties have been reported, in large part due to the tremendous efforts that have been put into the design and synthesis of novel π‐conjugated fused‐ring cores. [ 34‐38 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Previously, our group demonstrated that fused-ring aromatic lactones (FRAL) are efficient building blocks for high-performance copolymer donors. [50][51][52][53][54][55][56][57] In this work, we report the synthesis of a copolymer donor PBDTTPTP by using a novel tetracyclic bislactone unit, thieno[2 0 ,3 0 :5,6]pyrano [3,4d]thieno [3,2-b]pyran-4,9-dione (TPTP). Thanks to the strong electron-withdrawing properties and good coplanarity of TPTP, PBDTTPTP shows a relatively small E opt g of 1.65 eV, a deep HOMO level and good hole mobility, and exhibits good performance in STOPVs.…”
Section: Introductionmentioning
confidence: 99%